BDY637: Resource Modelling / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2021)
Mathematical modelling is invaluable in understanding the fundamental phenomena of natural resources. This course will give students a broad introduction to modelling scientific applications using ordinary differential equations, difference equations, and stochastic processes. This is a course that either required for students in the natural and mathematical sciences or addresses problems through mathematical models. This course emphasizes mathematical rigor and abstraction, fundamental mathematical skills, and college-level mathematical concepts and techniques; teach how to develop mathematical models and draw inferences from them. This course approved for the Mathematical Modelling requirement must demonstrate and provide a system for consistency in instruction and assessment of student achievement. This course also approved for the mathematical modeling requirement should engage students with mathematical concepts and techniques that prepare them for a variety of possible future courses and degrees.